2015
DOI: 10.7734/coseik.2015.28.6.707
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Transfer Length for a Seven-Wire Strandwith FBG Sensors

Abstract: In this paper, an experimental program has been conducted to investigate transfer length in high strength concrete members pretensioned through a seven-wire strand with FBG sensors. To measure transfer length, five members were fabricated, which had a length of 3 m and a cross-section of 150×150mm. It was measured that the concrete compressive strength was 58MPa at pretensioning. Test results indicated that more precise and reliable measurement on the transfer length was attained with FBG sensors than conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…By encapsulating the FBG sensor inside a seven-wire strand, the effective pre-stress force can be measured during construction and even during the service life of the product. In the literature, it was found that the effective pre-stress force can be accurately measured through FBG sensors, not only when tendons are directly exposed to the air [ 25 , 26 ], but also when tendons are embedded in concrete [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…By encapsulating the FBG sensor inside a seven-wire strand, the effective pre-stress force can be measured during construction and even during the service life of the product. In the literature, it was found that the effective pre-stress force can be accurately measured through FBG sensors, not only when tendons are directly exposed to the air [ 25 , 26 ], but also when tendons are embedded in concrete [ 27 ].…”
Section: Introductionmentioning
confidence: 99%